Low-Stakes Quizzing as a Predictor of Academic Outcomes: The Role of Motivation in Undergraduate Health Sciences Education. - Pérez Lizama, Miguel Ángel; Urrejola Contreras, Gabriela; Tiemann, Paula (Spanish Journal of Medical Education, 2025)
Introduction: Improving academic performance remains a central challenge in higher education. Test-enhanced learning (TEL) has been shown to improve knowledge retention and support long-term consolidation. However, the role of motivation in TEL contexts, particularly in low-stakes assessments, remains less well understood. This study examined the relationship between quiz performance, academic motivation, and subsequent outcomes in undergraduate health sciences students. Materials and Methods: A quasi-experimental design was conducted with 181 kinesiology students enrolled in Biology, Neurophysiology, and Pathophysiology courses. Over 16 weeks, students completed cumulative quizzes, mid-unit tests, and a final exam. Academic motivation was assessed using the Academic Motivation Scale (AMS). Data were analyzed using descriptive statistics and Pearson correlations. Results: Significant positive correlations were observed between early quiz performance and first exam scores (r = 0.50–0.70, p < 0.0001). Strong correlations also emerged between average quiz performance and final course grades across all courses (r = 0.71–0.82, p < 0.0001), confirming the predictive value of low-stakes assessments. Motivation profiles indicated high levels of intrinsic (M = 6.1) and extrinsic motivation (M = 6.2), alongside low but variable levels of lack of motivation (M = 1.8). Elevated intrinsic and extrinsic motivation likely fostered quiz engagement, consistent with self-determination theory. A minority of students reported high lack of motivation, suggesting potential risk for disengagement and academic failure. Conclusion: These findings suggest that TEL is effective both as a learning enhancer and as an early diagnostic tool. Integrating motivational assessments with structured low-stakes testing may help optimize teaching strategies, provide timely support for at-risk students, and improve academic success in higher education.